PENGARUH RASIO KEUANGAN TERHADAP INITIAL RETURN SETELAH INITIAL PUBLIC OFFERINGS (IPO) PADA PERUSAHAAN PUBLIK DI INDONESIA - Sri Hermuningsih (Universitas Paramadina, 2014)
This research aims to examine the effect of financial ratios on initial returnafter Initial Public Offerings (IPO) at Indonesian public companies. Samples involved 51 companies listed at Indonesia Stock Exchange from 2012 to 2013. Samples were taken by using purposive sampling method. Multiple regression analysis method was used in this research.Result has showed that Debt to Equity Ratio (DER) has provided significant negative effect on initial return. Higher DER value will increase uncertainty among investors and it will diminish stock returns; hence, it also lower returns that the investors receive. Company size (SIZE) has given significant positive effect on initial return. Larger size of the company has created trust among investors the company has been growing and producing a high return; meanwhile variables of Current Ratio (CR), Earning Per Share (EPS) and company age (AGE) has no effect on initial return.